Pharmacokinetic profiles for oral and subcutaneous methotrexate in patients with Crohn's disease. Issue 3 (28th November 2012) - Wilson, A.; Patel, V.; Chande, N.; Ponich, T.; Urquhart, B.; Asher, L.; Choi, Y.; Tirona, R.; Kim, R. B.; Gregor, J. C.
Summary Background Methotrexate (MTX) is administered subcutaneously to Crohn's Disease (CD) patients. There are very few studies evaluating the use of oral (PO) MTX in CD. A drug and its pharmaceutical alternative are equivalent (bioequivalence) when the bioavailability of the alternative falls within 80–125% of the bioavailability of the standard (US Food and Drug Administration ‐ FDA). Aim To compare the pharmacokinetic (PK) profiles of PO and subcutaneous (SC) MTX in CD patients to determine the bioequivalence of these two routes. Methods Eleven patients received a PO and an SC MTX dose (25 mg) separated by one week over a two‐week interval. Blood samples were collected at specified times over a 24‐h period for each patient on two separate days. MTX plasma levels were obtained using sensitive mass spectrometry. Areas under the curve (AUC) were compared between the two routes. Results The mean AUC values were 3375 ng/mL × h (PO MTX) and 3985 ng/mL × h (SC MTX). The mean AUC ratio (PO/SC) was 0.86 (0.62–1.08). This correlates with a relative PO bioavailability of 86% in comparison to SC. The 90% confidence interval for the mean AUC (PO/SC) ratio is (0.785, 0.929). There were no adverse events. Conclusions The mean MTX AUC (PO/SC) in these patients falls outside the 90% confidence interval for the bioequivalence limit. SC MTX is more bioavailable than PO MTX; however, the mean relative MTX bioavailability (PO/SC) nearly met the FDA bioequivalence standard and PO MTX could be proposed in responders who would prefer this route.